2019
DOI: 10.1002/cae.22152
|View full text |Cite
|
Sign up to set email alerts
|

Virtualization and visualization of virtual memory system for effective teaching–learning

Abstract: In this paper we present a tool that virtualizes creation and execution of large address space programs, and visualizes working of virtual memory system in response to their virtualized execution to facilitate effective teaching-learning of the abstract concept and technical details of virtual memory system. The tool allows users to write large address space virtual programs using a small set of instructions, virtualize their execution and visualize the working of virtual memory system in response to their vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…They observed that age, gender, religious affiliation, and social contacts are necessary to understand before teaching someone “how to live in a pluralistic society.” Here, active learning plays an important role in emphasizing population knowledge and skills. Active learning is used to broaden students' thinking abilities and demonstrate the person's values and attitudes [5,17]. The authors have studied the importance of the active learning process in various important domains like health beliefs, behaviors and services, information and formal care of elderly persons, life during work, retirement and leisure, religious affiliations, individual preferences in habits, foods, and services.…”
Section: State‐of‐the‐artmentioning
confidence: 99%
“…They observed that age, gender, religious affiliation, and social contacts are necessary to understand before teaching someone “how to live in a pluralistic society.” Here, active learning plays an important role in emphasizing population knowledge and skills. Active learning is used to broaden students' thinking abilities and demonstrate the person's values and attitudes [5,17]. The authors have studied the importance of the active learning process in various important domains like health beliefs, behaviors and services, information and formal care of elderly persons, life during work, retirement and leisure, religious affiliations, individual preferences in habits, foods, and services.…”
Section: State‐of‐the‐artmentioning
confidence: 99%
“…There have been a number of simulation/visualization tools developed for virtual memory in the past ([5]- [13]). These visualizations tend to be written from an operating systems perspective, with a focus on the contents of virtual and physical memory using a fixed configuration and limited features.…”
Section: Figure 1 -Memory Systems -Idealized View Vs Memory Hierarchymentioning
confidence: 99%